The effect of bio-banding on the anthropometric, physical fitness and functional movement characteristics of academy soccer players - MacMaster, C.; Portas, M.; Parkin, G.; Cumming, S.; Wilcox, C.; Towlson, C. (PLOS ONE, 2021)
The study examined if maturity status bio-banding reduces within-group variance in anthropometric, physical fitness and functional movement characteristics of 319, under-14 and under-15 players from 19 UK professional soccer academies. Bio-banding reduced the within-bio-banded group variance for anthropometric values, when compared to an aggregated chronological banded group (chronological: 5.1-16.7%CV; bio-banded: 3.0-17.3%CV). Differences between these bio-banded groups ranged from moderate to very large (ES = 0.97 to 2.88). Physical performance variance (chronological: 4.8-24.9%CV; bio-banded: 3.8-26.5%CV) was also reduced with bio-banding compared to chronological aged grouping. However, not to the same extent as anthropometric values with only 68.3% of values reduced across banding methods compared to 92.6% for anthropometric data. Differences between the bio-banded groups physical qualities ranged from trivial to very large (ES = 0.00 to 3.00). The number of functional movement metrics and %CV reduced by bio-banding was lowest within the `circa-PHV` groups (11.1-44.4%). The proportion of players achieving the threshold value score of = 14 for the FMS™ was highest within the `post-PHV` group (50.0-53.7%). The use of maturity status bio-banding can create more homogenous groups which may encourage greater competitive equity. However, findings here support a bio-banding maturity effect hypothesis, whereby maturity status bio-banding has a heightened effect on controlling for characteristics which have a stronger association to biological growth.